(untitled) (Confluenţe Bibliologice, 2026)
This article examines the presence and significance of Hugo’s masterpiece within the USARB Scientific Library’s collection. It highlights how the editions of this novel, accessible to readers, illustrate the convergence of historical rigor (culture), the visual depiction of Gothic art (art), and narrative genius (literature), confirming the library’s role as a custodian of universal values.